Calcium‐sensing receptor gene polymorphism (rs7652589) is associated with calcium nephrolithiasis in the population of Yi nationality in Southwestern China. (16th April 2018) - Li, Hao; Zhang, Jianhua; Long, Jiang; Shi, Jiarun; Luo, Yuhui
Abstract: The calcium‐sensing receptor ( CaSR ) gene plays an important role in regulating the Ca 2+ balance and reducing the risk for calcium stones. In this study, we evaluated the association of CaSR polymorphisms with calcium nephrolithiasis in the population of Yi nationality in Southwestern China. Biochemical variables were evaluated in 624 calcium nephrolithiasis patients and 470 age‐matched healthy controls without a history of nephrolithiasis. CaSR polymorphisms rs7652589, rs1501899, rs1801725 (Ala986Ser), rs1042636 (Arg990Gly) and rs1801726 (Gln1011Glu) were investigated between the calcium nephrolithiasis patients and healthy controls, using direct sequencing. Compared with the healthy controls, serum creatinine and 24‐hour urine calcium levels were significantly higher in calcium nephrolithiasis patients. Among these five polymorphisms, the genotypic and allelic frequency distributions of rs7652589 SNP was significantly associated with the risk of calcium nephrolithiasis. However, there were no genotypic or allelic distribution differences for rs1501899, rs1801725, rs1042636, and rs1801726 polymorphisms between calcium nephrolithiasis patients and healthy controls. Moreover, the association between rs7652589 SNP genotypes and the biochemical variables was not found. Our study showed that CaSR rs7652589 polymorphism had a significant effect on the risk of developing calcium nephrolithiasis in the population of Yi nationality in Southwestern China.